(untitled) (Quinto Sol, 2012)
An intense process of state development, which generated social intervention and new capacities to produce public policies, took place since the forties in Argentina. This phenomenon was accompanied by trends towards an increasing centralization of the political power in the Executive branch of the government. Within this context, this paper attempts to explore these processes from a perspective based on a provincial jurisdiction, constructing an account that locates the history of this political entity within the more comprehensive story of the structuring of the Interventionist State. In order to achieve this purpose, the history of one provincial health department and its relationships with the Federal State organizations are analyzed, trying to unravel the reactions that the provincial state elaborated to the process of centralization of social policies, which accompanied the emergence of Peronism.